PENGARUH, LIKUIDITAS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PADA SUB SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2021 - Ni Putu Devi Anggraini Permatasari; Aminatuzzuhro Aminatuzzuhro (Jurnal Ekonomi, Bisnis dan Social, 2024)
This research aims to test and analyze the influence of leverage, liquidity and company size on profitability. In this research, the samples used were all banking sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. This research is research using a quantitative approach and secondary data in the form of financial report data. The sample for this research was obtained using the purposive sampling method, namely selecting samples using predetermined criteria. The data collection technique in this research uses secondary data, namely research data obtained by researchers indirectly but through intermediary media. The analysis technique used is multiple regression analysis using the Eviews program.